FUNCTIONAL ZONING FOR INTEGRATED COASTAL MANAGEMENT IN THAI BINH PROVINCE - Cu, Nguyen Van; Muon, Nguyen Van; Cuong, Nguyen Quoc; Huong, Bui Thi Thanh; Anh, Tran Thi Ngoc (Vietnam Journal of Marine Science and Technology, 2019)
On the basis of analyzing natural conditions, resources, current exploitation status and functional zoning principles and criteria, functional zoning maps for integrated coastal management in Thai Binh were incorporated. Results suggested classifying Thai Binh coasts into two functional zones: Urban and multi-economic development zone and ecological conservation and recovery with economic development and national defense zone. Then, zone 1 and zone 2 were classified into 3 and 4 different functional sub-regions respectively with suitable proposal of prior activities and management. This research is an important basis for coastal development and intergrated coastal management in Thai Binh.